(untitled) (Scientific journal of the Fergana State University, 2024)
The 21st century is the age of information technologies and social networks. In this regard, mass media is widely spread among the society and is becoming a convenient aspect of receiving and sending information quickly, conveying the mass culture of social networks. In addition, information literacy is essential for teachers to teach students about the benefits of future technology education, the dissemination of knowledge through social networks, and the convenience of teaching through new technologies. is an aspect. At the same time, the article provides information about the importance of media tools in the self-development of future technological education teachers, how to use them effectively, and how to coordinate them in the educational process.